Where do Russia's mobilized soldiers come from? Evidence from bank deposits - Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
Russia does not release information on the numbers of mobilized and recruited men or casualties of war in Ukraine. In this small note, I propose to use information from regional banking data as a proxy for analyzing the regional incidence of Russian mobilization. Some regions have seen rapid increases in household bank deposits not easily attributable to regional macroeconomic or institutional factors. Such regions coincide with the regions with proportionally large numbers of mobilized soldiers. It is plausible that the high salaries and hefty payments promised to contract soldiers, mobilized reservists and their families in the event of serious injury or death show up as spikes in regional bank deposits.
urn:nbn:fi-fe202402218090
Keywords: 330; Russia; regions; mobilization; war casualties; bank deposits